Clozapine prescription trends in Brazil in the last decade - Massuda, Raffael (2022)
Objective: Clozapine is a second-generation antipsychotic indicated for treatment-resistant schizophrenia. Studies in several countries have shown a low rate of clozapine use despite the fact that approximately 30% of schizophrenia cases are treatment-resistant. In Brazil, few studies have addressed the frequency and variety of antipsychotic use in individuals diagnosed with schizophrenia (ICD F20). The objective of this study was to measure the rates of clozapine use in this population in the last decade using Brazilian Ministry of Health data. Methods: Prescriptions made between 2010 and 2020 in all 26 states and the Federal District registered at the Outpatient Information System Database from the Brazilian Health System (SIASUS) were evaluated. Results: A total of 25,143,524 prescriptions were recorded in this period, with clozapine representing 8.86% of all antipsychotics. The most frequently prescribed antipsychotic for patients with schizophrenia was olanzapine (35.8%), followed by quetiapine (27.5%). From 2010 to 2020, the rate of clozapine prescriptions in Brazil increased from 7.2% to 10.9%. Conclusions: Despite a slight increase in prescriptions in the last decade, clozapine is still underutilized in Brazil.